2018
DOI: 10.1021/acs.jpcc.8b08733
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Catalytic Performance of Reconstructed Fe3O4(001) and Fe3O4(110) Surfaces during Oxygen Evolution Reaction

Abstract: Earth-abundant oxides are promising candidates as effective and low-cost catalysts for the oxygen evolution reaction (OER) in alkaline media, which remains one of the bottlenecks in electrolysis and artificial photosynthesis. A fundamental understanding of the atomic-scale reaction mechanism during OER could drive further progress, but a stable model system has yet to be provided. Here we show that Fe3O4 single crystal surfaces, prepared in ultrahigh vacuum (UHV) are stable in alkaline electrolytein the range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…The Fe 3 O 4 (001) CTRs exhibit minor changes during the lifting of the reconstruction, suggesting that the latter is a pure surface phase transition and does not involve substantial restructuring or roughening of the surface. This is in agreement with recent ex situ AFM observations of Fe 3 O 4 (001) immersed in aqueous electrolyte solution [4] . However, pronounced irreversible roughening occurs after changing the potential to even more negative values of ≤−1.20 V, where reduction of the Fe oxide to Fe 0 commences (Figure S5) [7]…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…The Fe 3 O 4 (001) CTRs exhibit minor changes during the lifting of the reconstruction, suggesting that the latter is a pure surface phase transition and does not involve substantial restructuring or roughening of the surface. This is in agreement with recent ex situ AFM observations of Fe 3 O 4 (001) immersed in aqueous electrolyte solution [4] . However, pronounced irreversible roughening occurs after changing the potential to even more negative values of ≤−1.20 V, where reduction of the Fe oxide to Fe 0 commences (Figure S5) [7]…”
Section: Figuresupporting
confidence: 91%
“…While the structure of Fe 3 O 4 (001) is well known in UHV, it is not clear whether the surface changes in aqueous solution. Atomic force microscopy (AFM) studies have shown that the nanoscale morphological appearance of Fe 3 O 4 (001) is maintained in an electrochemical environment, [4] but recent work suggests the reconstruction is lifted by exposure to 6 mbar water vapor, as well as by pure liquid water at pH 7 [5] . This is in line with previous surface X‐ray diffraction measurements, which also found the reconstruction to be lifted by water vapor [3] .…”
Section: Figuresupporting
confidence: 75%
“…Nanocarbon materials used as catalyst supports often need to be optimized, such as by adjusting the pore size, doping heteroatoms, constructing defect sites, and others [227]. Additionally, different nanocarbon materials have different characteristics, so a composite carbon material combining two or more nanocarbon materials as a catalyst support [11,[228][229][230] may complement each other with advantages, thereby exhibiting better performance. Compared with the classical metal-supported catalyst model, the metal-organic framework (MOF)-based catalysts have better structure and chemical property controllability and their huge potential cannot be ignored [231].…”
Section: Discussionmentioning
confidence: 99%
“…[2] While the structure of Fe 3 O 4 (001) is well known in UHV, it is not clear whether the surface changes in aqueous solution. Atomic force microscopy (AFM) studies have shown that the nanoscale morphological appearance of Fe 3 O 4 (001) is maintained in an electrochemical environment, [4] but recent work suggests the reconstruction is lifted by exposure to 6 mbar water vapor, as well as by pure liquid water at pH 7. [5] This is in line with previous surface X-ray diffraction measurements, which also found the reconstruction to be lifted by water vapor.…”
mentioning
confidence: 99%
“…This is in agreement with recent ex situ AFM observations of Fe 3 O 4 (001) immersed in aqueous electrolyte solution. [4] However, pronounced irreversible roughening occurs after changing the potential to even more negative values of À1.20 V, where reduction of the Fe oxide to Fe 0 commences (Figure S5). [7] In contrast to the behavior at negative potentials, the reconstruction is remarkably stable at potentials where oxygen evolution commences.…”
mentioning
confidence: 99%